2016
DOI: 10.1111/hepr.12825
|View full text |Cite
|
Sign up to set email alerts
|

Increased lipogenesis in spite of upregulated hepatic 5'AMP‐activated protein kinase in human non‐alcoholic fatty liver

Abstract: In humans with advanced fatty liver disease, hepatic AMPK protein is upregulated, potentially in a compensatory manner. Moreover, pathways of lipid synthesis and degradation are co-activated in subjects with advanced steatosis. Palmitate may drive lipogenesis by activating XBP1-mediated endoplasmic reticulum stress and represent a target for future dietary or pharmacological intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…In addition, palmitate, contained in HFCD, may induce lipogenesis by activating X-Box binding protein-1-mediated endoplasmic reticulum stress, demonstrated by the increase in steatosis score ≥2, associated with blood palmitate (68,69). In the normal rat group, the physiological level of SCD-1 maintained a balanced ratio of MUSFA/SFA to keep the hepatic tissue healthy without fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, palmitate, contained in HFCD, may induce lipogenesis by activating X-Box binding protein-1-mediated endoplasmic reticulum stress, demonstrated by the increase in steatosis score ≥2, associated with blood palmitate (68,69). In the normal rat group, the physiological level of SCD-1 maintained a balanced ratio of MUSFA/SFA to keep the hepatic tissue healthy without fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, evidence has indicated that SCD-1 overexpression is associated with liver fibrosis and hepatocellular carcinoma (68,70). In addition, a high fructose diet prolonged hepatic SCD-1 activation and promoted TG accumulation and steatosis (71,72).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies of FAO in patients with or NASH are conflicting, reporting enhanced [118][119][120], unchanged [121], or decreased FAO [122]. The expression of genes related to mitochondrial and peroxisomal β-oxidation was higher in patients with more severe steatosis than in individuals with less severe steatosis or in nonsteatotic controls [123]. Additionally, β-oxidation, measured indirectly as plasma β-hydroxybutyrate levels, was higher in patients with NASH than in those with steatosis or normal controls [120].…”
Section: Fatty Acid Oxidation and Vldl Secretionmentioning
confidence: 98%
“…Pharmacological inhibition of sodium-coupled citrate transporter. Slc13a5 deletion and pharmacological inhibition ameliorate obesity, insulin resistance, and NAFLD in various model organisms (Birkenfeld et al, 2011;Shulman and Helfand, 2011;Willmes and Birkenfeld, 2013;Neuschäfer-Rube et al, 2014;Huard et al, 2015;Pesta et al, 2015;Brachs et al, 2016;Willmes et al, 2016Willmes et al, , 2018Rogina, 2017;von Loeffelholz et al, 2017a). NaCT has therefore been proposed as a promising target for the prevention and treatment of metabolic diseases.…”
Section: Skeletal Musclementioning
confidence: 99%